Does being on HIV antiretroviral therapy increase the risk of syphilis? An analysis of a large national cohort of MSM living with HIV in England 2009–2016. Issue 3 (10th November 2020) - Allen, Hester; Kirwan, Peter; Brown, Alison E; Mohammed, Hamish; Hughes, Gwenda; Marks, Michael; Delpech, Valerie
Abstract : Objective: A resurgence in bacterial STIs, notably syphilis, among gay, bisexual and other men who have sex with men (MSM) has been detected in England. A Canadian modelling study postulated that antiretroviral therapy (ART) may increase susceptibility to syphilis. We assess the association between ART and syphilis incidence in a comprehensive national cohort of MSM living with HIV in England. Methods: National surveillance data were used to create a cohort of MSM attending for both HIV and STI care in England between 2009 and 2016. Survival analysis was used to calculate the incidence of infectious syphilis during periods on and off ART. Multivariable Poisson regression was used to assess the association between ART use and syphilis, after adjustment for potential confounders, including, as a proxy measure for high-risk behaviour, being diagnosed with >1 other STI prior to a syphilis diagnosis. Results: 19 428 HIV diagnosed MSM contributed 112 960 person-years of follow-up from 2009 to 2016. The overall rate of syphilis was 78.0 cases per 1000 person-years follow-up. Syphilis rates were higher among men receiving ART (36.8) compared with those who did not (28.4) (absolute rate difference 4.7 cases per 1000 person-years). Multivariable analysis showed no statistical association between receiving ART and syphilis. Increased risk of syphilis was found in MSM aged 25–34 (HR 1.89, 95% CI 1.43 to 2.51) and in those diagnosed with two other STIs (HR 5.83, 95% CI 5.37 to 6.32). Conclusion: While we observed a small increase in the rate of syphilis among those on ART, when adjusting for potential confounding factors, including a proxy measure for high-risk behaviour, there was no evidence of an increased risk of syphilis in MSM receiving ART. High-risk sexual behaviour markers were the main risk factors for syphilis, and our results highlight the need for STI prevention interventions in MSM living with HIV to target these particularly high-risk sexual networks.